(untitled) (Fiep Bulletin - online, 2014)
Objective: Stroke (CVA) is a disabling neurological disease that can be hemorrhagic or ischemic region and undertake a greater or lesser brain, causing different symptoms each patient. The main clinical sign is hemiplegia, which is the commitment of one side of the body formed by motor, sensory and cognitive. By causing deficits to the individual, the AVE leaves the patient partially or totally dependent in their activities of daily living (ADLs), this dependence that affects the quality of life (QOL) of the same. By applying the Barthel Index (BI) can score the functional dependence of the individual. In addition to identifying functional impairment, standardized questionnaires are used to assess the impact of the disease, such as quality of life questionnaire SF -36. The present study aims to quantify the level of functional capacity and quality of life interference in eleven patients affected by stroke. Methodology: Study of a quantitative, qualitative and epidemiological conducted at Rehabilitation FAG with the population affected by stroke in the period from July to September, which was applied to the Barthel Index and quality of life questionnaire SF - 36 and the results were exposed in the form of simple graphic. Results: patients affected by stroke showed some degree of dependence on their ADLs associated with a poor quality of life. Conclusion: It was concluded in this study that this neurologic disease negatively affects the lives of individuals affected , causing functional and cognitive deficits that lead to poor quality of life . However , there are few studies that address the relationship of stroke with functional disability and use of indices and scales .